Quantification of competitive game demands of NCAA Division I college football players using global positioning systems - Wellman, A. D.; Coad, S. C.; Goulet, G. C.; McLellan, C. P. (The Journal of Strength and Conditioning Research, 2016)
The aim of the present study was to examine the competitive physiological movement demands of National Collegiate Athletic Association (NCAA) Division I college football players using portable global positioning system (GPS) technology during games and to examine positional groups within offensive and defensive teams, to determine if a player's physiological requirements during games are influenced by playing position. Thirty-three NCAA Division I Football Bowl Subdivision football players were monitored using GPS receivers with integrated accelerometers (GPSports) during 12 regular season games throughout the 2014 season. Individual data sets (n = 295) from players were divided into offensive and defensive teams and subsequent position groups. Movement profile characteristics, including total, low-intensity, moderate-intensity, high-intensity, and sprint running distances (m), sprint counts, and acceleration and deceleration efforts, were assessed during games. A one-way ANOVA and post-hoc Bonferroni statistical analysis were used to determine differences in movement profiles between each position group within offensive and defensive teams. For both offensive and defensive teams, significant (p = 0.05) differences exist between positional groups for game physical performance requirements. The results of the present study identified that wide receivers and defensive backs completed significantly (p = 0.05) greater total distance, high-intensity running, sprint distance, and high-intensity acceleration and deceleration efforts than their respective offensive and defensive positional groups. Data from the present study provide novel quantification of position-specific physical demands of college football games and support the use of position-specific training in the preparation of NCAA Division I college football players for competition.